Crystallization and preliminary X‐ray diffraction studies of an L‐amino‐acid oxidase from Lachesis muta venom. Issue 11 (5th November 2014) - Ullah, Anwar; Masood, Rehana; Spencer, Patrick Jack; Murakami, Mário Tyago; Arni, Raghuvir Krishnaswamy
<x xml:space="preserve">Abstract</x> Snake‐venom proteins form multi‐component defence systems by the recruitment and rapid evolution of nonvenomous proteins and hence serve as model systems to understand the structural modifications that result in toxicity. L‐Amino‐acid oxidases (LAAOs) are encountered in a number of snake venoms and have been implicated in the inhibition of platelet aggregation, cytotoxicity, haemolysis, apoptosis and haemorrhage. An L‐amino‐acid oxidase from Lachesis muta venom has been purified and crystallized. The crystals belonged to space group P21, with unit‐cell parameters a = 66.05, b = 79.41, c = 100.52 Å, β = 96.55°. The asymmetric unit contained two molecules and the structure has been determined and partially refined at 3.0 Å resolution.